The Development of Three Tier Test (TTT) Instruments to Identify Students Misconceptions on Material in Elementary - Suci Zakiah Dewi; Irfan Hilman (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
The purpose of this study is to develop the assessment instruments used in testing the level of science misconceptions in high grade elementary school. The instrument used is a Three-tier test (TTT) This research is a Research and Development (R&D) research that is a method of conducting research for research that produces a product, and testing the effectiveness of the product. The research stages are as follows: (1) Data Collection and Literature Studies, (2) Product Description and Design, (3) Small Scale Trials, (4) Product Analysis and Revision, (5) Broad-Scale Trials, and (6) Product Analysis and Revision. The research conducted at SDN 5 Sukagalih, Tarogong Kidul District, Garut on a small scale and for a large scale at SDN 1,2,3,4 and 5 Sukagalih, Tarogong Kidul District, Garut. Based on the results of the research obtained data that by using TTT instruments teachers can find out how much quantity of students are misconceptions, trials are conducted on a small scale and large scale and each is carried out 2 stages, namely the stage before the revision and after the revision of the instrument. The results of phase I tests on a large scale many students experienced misconceptions of 62.7% and the phase II test after instrument revision showed a significant decrease to 32.65% of students who experienced misconceptions, the presentation of a decrease in the quantity of misconceptions for large scale was 52.86%. the result was quite significant compared to the small scale which decreased by only 24.61%. The results showed that by using TTT techniques teachers will easily identify the quantity of students who misconception and for the next the teacher will provide treatment to students to lower the quantity.